Marketing a new African God: Pentecostalism and material salvation in Ghana - Bonsu, Samuel K.; Belk, Russell W. (International Journal of Nonprofit and Voluntary Sector Marketing, 2010)
Pentecostalism is an American creation that has been exported to various parts of theworld. Its message of hope is produced and promoted by churches that are led by religiousentrepreneurial salespeople who create value for customers through the use of marketingtechniques that facilitate the blending of the local and the global; the sacred and theprofane. Its success in Africa has been attributed to the African penchant for connectingevery human experience to the religious. Using the marketing strategic framework oftarget market and four Ps as an organization tool, we draw on a year-long ethnographyin Kumasi, Ghana, to suggest that Pentecostalism in Ghana is marketed as an effectiveroute to material success without risk to postmortem salvation. While the effective blendof the sacred and the profane allows for open public discourse, it fails to deliver on itspromise of economic salvation for the poor. In fact, it causes the condition of the poor todeteriorate even further through application of its fundamental requirement: give andGod will bless you according to the extent of your giving. We conclude that the newAfrican Pentecostalism and its open embrace of contemporary consumption and materi-alism have arrested local religiosity and imposed an ‘‘economic imperialism’’ thatimpregnates every human experience with a commercial character.
free